Brachial Plexus Injuries with Ulnar Musculocutaneous Transfer: 78 Cases Study Focused on Possible Postoperative Complications - Corrêa, Márcio Gargalhone; Cardoso, Márcio de Mendonça; Gepp, Ricardo de Amoreira; Quiroga, Marco Rolando Sainz; Beraldo, Paulo Sérgio Siebra (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2019)
Objective To analyze 78 cases of brachial plexus injury submitted to the Oberlin technique between 2003 and 2012. The potential complications of this technique were analyzed, especially motor damage or hypoesthesia of the hand.Method Medical records from patients with brachial plexus injuries at the levels of the C5-C6 and C5-C6-C7 vertebrae were retrospectively analyzed. Cases submitted to the Oberlin procedure with or without concomitant brachial plexus procedures between 2003 and 2012 were evaluated. The minimum follow-up period was of 1 year. In addition to the clinical examination, electromyography and magnetic resonance imaging (MRI) of the brachial plexus were used to diagnose and locate the nerve damage.Results A total of 78 surgical patients met the inclusion criteria. Postoperative neurological changes, mostly transient, were observed in 18 patients. Hypoesthesia in the ulnar side of the hand was observed in seven cases; neuropathic pain in five cases; allodynia in four cases, and hand motor loss in two cases.Conclusion Based on the results of the present case series, we conclude that there are few sequelae in the donor nerve territory compared with the benefit of the Oberlin technique on the recovery of elbow flexion after brachial plexus injuries.
Keywords: nerve transfer; ulnar nerve; musculocutaneous nerve